2010
DOI: 10.1128/aem.01206-10
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis of Strains of Lactic Acid Bacteria and Acetic Acid Bacteria in Cocoa Pulp Simulation Media toward Development of a Starter Culture for Cocoa Bean Fermentation

Abstract: The composition of cocoa pulp simulation media (PSM) was optimized with species-specific strains of lactic acid bacteria (PSM-LAB) and acetic acid bacteria (PSM-AAB). Also, laboratory fermentations were carried out in PSM to investigate growth and metabolite production of strains of Lactobacillus plantarum and Lactobacillus fermentum and of Acetobacter pasteurianus isolated from Ghanaian cocoa bean heap fermentations, in view of the development of a defined starter culture. In a first step, a selection of stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
108
2
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(121 citation statements)
references
References 33 publications
5
108
2
6
Order By: Relevance
“…was later found in the inoculated fermentation than in the spontaneous fermentation. LAB convert carbohydrates and citric acid into lactic acid from the second day of cocoa fermentation (Camu et al 2007;Lefeber et al 2010Lefeber et al , 2012. However, recent research suggests that LAB may not be necessary for successful cocoa fermentation due beans fermented in the presence or absence of lactic acid bacteria are fully fermented, have similar shell weights and produce acceptable chocolates with no differences in sensory rankings (Ho et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…was later found in the inoculated fermentation than in the spontaneous fermentation. LAB convert carbohydrates and citric acid into lactic acid from the second day of cocoa fermentation (Camu et al 2007;Lefeber et al 2010Lefeber et al , 2012. However, recent research suggests that LAB may not be necessary for successful cocoa fermentation due beans fermented in the presence or absence of lactic acid bacteria are fully fermented, have similar shell weights and produce acceptable chocolates with no differences in sensory rankings (Ho et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These substrates are used for the oxidation of NADH ϩ H ϩ to bypass the energy-limiting ethanol pathway and, so, to maximize their growth rate on glucose, thereby producing mannitol and lactic acid plus acetic acid, respectively (16). They are to be consumed under low-pH and anaerobic conditions in the beginning of the cocoa bean fermentation.…”
mentioning
confidence: 99%
“…During fermentation, bacterial growth (CFU per ml) was quantified through plating of 10-fold serial dilutions of the samples in saline (0.85% [wt/vol] NaCl solution) on CPSM agar (CPSM containing 1.5% [wt/vol] agar, pH 5.5) that was incubated at the appropriate fermentation temperature for 24 h. Metabolite concentrations were determined through high-performance anion-exchange chromatography using a standard addition protocol (glucose, fructose, mannitol, and citric acid) (15,23) and high-performance liquid chromatography using external standards (lactic acid, acetic acid, and ethanol) (16). Cell count and metabolite (with external standards) measurements were performed on three independent samples.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This observation was not the same for Gluconobacter genera. The same observation has been regularly recorded in cocoa beans fermentation According to these authors, from the 10 existing genera of AAB, only the Acetobacter and Gluconobacter reported to colonize cocoa beans fermenting mass the Acetobacter genus dominant [51,52 genus is known to oxidize ethanol to acetic acid and species from the genus Acetobacter have the additional capacity to oxidize acetic acid to carbon dioxide and water known that production of acetic acid during cocoa fermentation is desirable for development of precursors chocolate aroma [54,55]. At date, the possible impact of the balance between both types of AAB, on the quality of bean is not established.…”
Section: Total Of Isolates Mal Lac Galmentioning
confidence: 78%